Secure File Storage System Using Cloud - Sudhanshu M. Wasu,; Dr. Sudhir W. Mohod, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Cloud computing basically comes to focus on IT, a way to increase capacity or add potentiality on the fly without investing in new infrastructure, training new personnel, or licensing new software. It encompasses any subscription-based or pay-per-use service that, in real time over the Internet, extends its existing capabilities. It is often provided "as a service" over the Internet, typically in the form of infrastructure as a service (IaaS), platform as a service (PaaS), or software as a service (SaaS). Microsoft Azure and Google App Engine are the examples of platform as a service. The fast growth in field of "cloud computing" also increases rigorous security concerns. In today’s world most of the communication is done using electronic media. Data Security is widely used to ensure security in communication, data storage and transmission. We have Advanced Encryption Standard (AES) which is accepted as a symmetric cryptography standard for transferring block of data securely. The available AES algorithm is used for text data and it is also suitable for image encryption and decryption to protect the confidential image data from an unauthorized access. This project proposes a method in which the image data is an input to AES Encryption to obtain the encrypted image, and the encrypted image is the input to AES Decryption to get the original image.
Keywords: Cloud Computing; Security; Encryption; Decryption; AES; DES